Why Patients Refuse to Enroll in Hospital-Based Research: Perception of Patients Presenting to KATH Emergency Department. Issue Volume 34:Issue s1(2019) (May 2019) - Bonney, Joseph; Amissah, Esi; Cobbold, Sonia; Forson, Paa Kobina
Abstract : Introduction: Komfo Anokye Teaching Hospital Emergency Department (KATH ED) is a tertiary referral center in Ghana. Anecdotally, patients seeking care at KATH ED do not actively participate in research initiatives. Aim: To find out why patients presenting to KATH ED do not enroll in research studies that are conducted in the department. Methods: The study was a cross-sectional survey of patients presenting to the ED for one month in June 2017. A semi-structured questionnaire was presented to patients presenting to KATH ED from 8:00-20:00 each day. Patients who were interviewed were all patients presenting to the ED for care, including those who had refused to enroll in the ongoing ACESO study. Patients had to be conscious, alert, and with conditions that did not require immediate management. Results: 35% of the interviewees (91/260) had been approached to enroll in research studies at some point in the past. 13.5% had refused to enroll in a research study. 45.7% of those who refused to enroll admitted that they were afraid to enroll in a study; 28.6% had inadequate information and 22.9% perceived enrolling in a study would delay their treatment. The Akan language (73%) was most commonly used by research assistants then English (26%), and finally Hausa (1%) to interact with patients. There was a significant association between educational background and explaining a study to a patient before they enrolled. Males were more willing to enroll in an ongoing study compared to females. All age groups correlated significantly with being approached to enroll in a research study and similarly all age groups also correlated with refusing to enroll in a research study Discussion: Patients are paramount to hospital research. Efforts must be made to ensure that patients concerns and needs are addressed to ensure increasing participation.